(untitled) (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2015)
In this study were analyzed descriptively inflation, money supply and the interest rate on deposits in Indonesia. The data used is secondary data directly on the object of research studies and data already available on the website of Bank Indonesia and the Ministry of Finance. Several previous studies have been conducted to look at the relationship and want to know the condition of inflation, the money supply and interest rates on deposits in Indonesia. Supported by several theories about Inflation, Money Supply and Interest Rate Deposit, this research can be done to look at the various influences of these variables. The method used is descriptive analysis. The purpose of this study was to determine the condition of Inflation, Money Supply and Interest Rate Deposit in Indonesia. These results indicate that the variables Inflation, Money Supply and Interest Rate Deposit in Indonesia. These results indicate that inflation and interest rates on deposits experienced while money beredarar fluctuate from year to year increase.